1995
DOI: 10.1007/bf00193697
|View full text |Cite
|
Sign up to set email alerts
|

Patient compliance and therapeutic coverage: comparison of amlodipine and slow release nifedipine in the treatment of hypertension

Abstract: To study patient compliance in hypertensive outpatients amlodipine (5 mg once daily) and slow release nifedipine (20 mg twice daily) were compared in an open, crossover study in general practices. Four methods of assessment for patient compliance (pill count, taking compliance, days with correct dosing, timing compliance) were used in both study arms. For the latter three assessment a special device, the medication event monitoring system, was used to record the time and date of each opening and closure of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(20 citation statements)
references
References 17 publications
1
18
0
1
Order By: Relevance
“…While adherence in general was fair, 30% of patients were adherent only to some drugs while exposure to other drugs was absent. This is compatible with the notion that nonadherence can happen consciously as well as unconsciously [26]. As expected [27], in our study nonadherence modestly increased with the number of drugs the patient had been prescribed.…”
Section: Discussionsupporting
confidence: 92%
“…While adherence in general was fair, 30% of patients were adherent only to some drugs while exposure to other drugs was absent. This is compatible with the notion that nonadherence can happen consciously as well as unconsciously [26]. As expected [27], in our study nonadherence modestly increased with the number of drugs the patient had been prescribed.…”
Section: Discussionsupporting
confidence: 92%
“…[13][14][15] Three recent studies using electronic pill boxes have also shown a lower compliance when using twice daily drugs compared to once daily drugs. 8,16,17 By extrapolation, it may seem obvious that compliance should be better in patients treated by a single drug rather than several. Our results suggest just the opposite; compliance increased with the number of drugs prescribed.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple diseases and complex medicine regimes in elderly patients may compromise adherence even further [3,4]. Studies of regimen simplification, like reduced dose frequency, often focus on patient adherence only and fail to include measures of satisfaction or acceptability by patients or show that simplification leads to clinical improvements [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 98%